Intestinal Evisceration in Domestic Violence: A Stab Wound Injury - AS, Nur Hayati (IIUM Medical Journal Malaysia, 2019)
A 9-year-old girl, waken up from sleep with acute abdomen. Noted by care-taker, evisceration of small bowels from a stab wound at the epigastric region. She was brought to ED with class II shock and mild pallor. Her caretaker lodged a police report after noticed her schizophrenic uncle left home with a knife. Following adequate resuscitation, she had emergency laparotomy. A moderate gastric content contamination with multiple sites of perforation at the stomach, small bowels and its mesentery was seen and repaired primarily. Postoperatively, she was ventilated in ICU, provided with parenteral nutrition and institution of broad-spectrum antibiotics. She was extubated and transferred to HDW on day 4 and make a complete recovery on day 10. Discussion: Paediatric penetrating abdominal injury is much less common as compared to blunt abdominal injury. It is important to determine the mechanism of injury as it influences the management decision. The colon and small bowels are the most commonly injured hollow organs in penetrating injury. A bowel injury in trauma is a leading cause of morbidity and mortality. Managing postoperative bowel injury in paediatric required a multidisciplinary team approach for a successful outcome. A well-prepared surgical team with a well-equipped operation room, availability of blood substitutes and the necessary investigations are all the important links in the management of the patient of bowel evisceration.